Implementasi Pengendali PID Pada Pendaratan Otomatis Wahana Tanpa Awak - Juvindi Walalangi; Vecky C. Poekoel; Feisy D. Kambey (Universitas Sam Ratulangi, 2018)
Abstract — Technological developments in aviation and aeromodelling, especially UAV (Unmanned aerial vehicle) type of fixed wing is growing. A fixed wing UAV is a plane that has a fixed wing shape, and uses wind or air pressure to generate lift. In flight, landing phase is the most critical phase, especially landing UAV type fixed wing because at the time of landing either with manual mode or automatic the aircraft must be well controlled. This final project has a title